HYDRAULIC PARAMETERS AND MORPHOMETRIC VARIABLES INTERACTIONS IN BEDROCK CHANNEL - Biswas, Biswajit; Chandra Das, Balai (Quaestiones Geographicae, 2016)
Present study is on the interdependent nature of hydraulic parameters and morphometric variables of a bedrock river. In this study, using dumpy level, GPS, satellite images and some mathematical equations a data set on hydraulics and morphometric variables of a bedrock channel, named Bhatajhor, of eastern India was generated. That data set was used to (1) find out impulse-response relations between hydraulic variables (2) find out relations between morphometric variables and (3) find out relations between hydraulic and morphometric variables. Seven equations (5–11) were formulated based on this empirical study to the end. The seven empirical relations, most of which include only two variables, involve channel cross-section dimensions (area, width, mean depth, maximum depth, width/depth ratio, hydraulic radius), slope and hydraulic variables (velocity, kinetic energy, stream power, Manning’s n factor, Chezy’s C factor and shear stress). Observation shows relatively higher coefficient of determination (R2) between variables like velocity and Manning’s n factor (0.67), velocity and Chezy’s C factor (0.67), slope and τ (0.89), w/d ratio and hydraulic radius (0.53), slope and w/d ratio (0.50).